Is self-esteem a "double edged sword"? Self-esteem and the onset of adolescent sexual activity - Marta Favara (Institute for the Study of Labor (IZA), 2013)
Self-esteem has been conceptualized as a social vaccine. The belief is that high self-esteem can inoculate young people, against vulnerability to a wide range of social illnesses. This study gives a contribution in the understanding of the causal relation between self-esteem and sexual behaviour among American adolescents. I analyzes the impact of different levels of early self-esteem on a wide set of risky sexual behaviours. I use data from the National Longitudinal Study of Adolescent Health and I take into account the endogeneity of self-esteem using instrumental variables methods and measuring self-esteem before sexual initiation. I find that self-esteem over a certain threshold' is a protective resource for girls, delaying the onset of sexual activity, reducing the number of occasional sexual partners and increasing the likelihood of having protected sexual encounters.
Keywords: I12; J13; O51; 330; self-esteem; adolescent's sexual behaviour; Add Health; instrumental variable model